(untitled) (Journal of Pharmaceutical Negative Results, 2023)
The objectives of this study were to investigate the effect of yogic practices on mental well being among school children. The subjects of the study were 40male students (20 subjects were kept on Experimental group and 20subjects were kept in Control group) from D.S.INTER COLLEGE, Aligarh. Age ranged the student between 14-17 years. Criterion measures for this study was Mental Well-being Scale (WEMWBS) (in rating) was administrated. To find out significant difference between two groups i.e. control and experimental groups Paired sample t-test was employed. The result of the data reveals the significant difference was found in experimental group insignificant difference was found in control group.